The effects of stabilizing treatment on microstructure and corrosion resistance of 316Ti stainless steel. (November 2019) - Zhao, Boshen; Zhao, Wenbo; Shi, Hongqi; Li, Guangzhou; Ding, Yi
Abstract: 316Ti stainless steel (316Ti) is given a stabilizing treatment in order to improve the intergranular corrosion resistance and service life. The parameters of 316Ti heat treatment were optimized in this work. The microstructure and intergranular corrosion resistance of 316Ti has been characterized by means of double-loop electrochemical potentiokinetic reactivation (DL-EPR), optical microscope (OM) and scanning electron microscope (SEM) with energy dispersive spectroscopy (EDS) analysis. The results show that the intergranular corrosion resistance increased with increasing aging temperature. Also, the titanium carbonitrides were formed in the substrate during the stabilizing treatment and the size increased with increasing aging time. Moreover, the relation of the amount of precipitated phases with intergranular corrosion resistance in 316Ti was established. Highlights: An optimized stabilization heat treatment for 316Ti is explored to modify the intergranular corrosion resistance. The relation of the amount of precipitated phases (TiCN) with intergranular corrosion resistance in 316Ti was proved. The intergranular corrosion resistance of 316Ti stainless steel could be measured accurately by DL-EPR.